PENGARUH PARTISIPASI PENGANGGARAN DAN INFORMASI ASIMETRI PADA SENJANGAN ANGGARAN DENGAN BUDAYA ORGANISASI SEBAGAI VARIABEL MODERASI - Gede Andy Mercury; I G.A.M. Asri Dwija Putri (Accounting Department, Economic and Business Faculty of Universitas Udayana in collaboration with the Association of Accounting Department of Indonesia, Bali Region, 2015)
This research has purpose to provide additional empirical evidence about the effect of budgetary participation and asymmetry information in budgetary slack with cultural organization as a moderating variable. This research sample consisted 46 stars hotels in Gianyar Regency. The data collection method that have been used is a questionnaires that distributed to the manager or head section/division that has a same level with the manager, this section has a functional in large role in used, management, and budgetary responsibility, also able to communicate with the subordinates and the top management, and participate as well with the wisdom that implemented by the top management in each of five stars hotel in Gianyar Regency. Data analysis tecnique that have been used is Moderated Regression Analysis (MRA). Based on the analysis results, it shows that budgetary participation and asymmetry information gives positive influences in budgetary slack. The interaction between budgetary participation with organization cultural be able to weaken the effect of asymmetry information in budgetary slack.